Impact of screening and doxycycline prevention on the syphilis epidemic among men who have sex with men in British Columbia: a mathematical modelling studyResearch in context - Jielin Zhu; Bronhilda T. Takeh; Jummy David; Jordan Sang; David M. Moore; Mark Hull; Troy Grennan; Jason Wong; Julio S.G. Montaner; Viviane D. Lima (Elsevier, 2024)
Summary: Background: Men who have sex with men (MSM) in British Columbia (BC) are disproportionately affected by infectious syphilis and HIV. In this study, we developed a co-interaction model and evaluated the impact and effectiveness of possible interventions among different MSM subgroups on the syphilis epidemic. Methods: We designed a deterministic compartmental model, which stratified MSM by HIV status and HIV pre-exposure prophylaxis (HIV-PrEP) usage into (1) HIV-negative/unaware MSM (HIV-PrEP not recommended, not on HIV-PrEP), (2) HIV-negative/unaware MSM with HIV-PrEP recommended (not on HIV-PrEP), (3) HIV-negative/unaware MSM actively on HIV-PrEP, and (4) MSM diagnosed with HIV. We estimated the effect of scaling up syphilis testing frequency from Status Quo to six-, four-, and three-months, increasing the percentage of MSM using doxycycline prevention (Doxy-P) to 25%, 50%, and 100% of the target level, and a combination of both among subgroups (2)-(4). We also assessed the impact of these interventions on the syphilis incidence rates from 2020 to 2034 in comparison to the Status Quo scenario where no intervention was introduced. Findings: Under the Status Quo scenario, with the expansion of the HIV-PrEP program to improve syphilis testing, the syphilis incidence rate was estimated to peak at 16.1 [Credible Interval (CI):14.2-17.9] per 1,000 person-years (PYs) in 2023 and decrease to 6.7 (CI:3.8-10.9) per 1,000 PYs by 2034. The syphilis incidence rate in 2034 was estimated at 0.7 (0.3-1.3) per 1,000 PYs if MSM diagnosed with HIV could be tested every four months, and at 1.5 (0.7-3.0) per 1,000 PYs if HIV-negative/unaware MSM actively on HIV-PrEP could be tested every three months. By achieving 100% of the target coverage of Doxy-P, the syphilis incidence rate was estimated at 1.4 (0.5-3.4) if focusing on MSM diagnosed with HIV, and 2.6 (1.2-5.1) per 1,000 PYs if focusing on HIV-negative/unaware MSM actively on HIV-PrEP. Under the combined interventions, the syphilis incidence rate could be as low as 0.0 (0.0-0.1) and 0.8 (0.3-1.8) per 1,000 PYs, respectively. Interpretation: The HIV-PrEP program in BC plays a crucial role in increasing syphilis testing frequency among high-risk MSM and reducing syphilis transmission among this group. In addition, introducing Doxy-P can be an effective complementary strategy to minimize syphilis incidence, especially among MSM diagnosed with HIV. Funding: This work was funded by the Canadian Institutes of Health Research.